A review of probiotics in the treatment of autism spectrum disorders: Perspectives from the gut–brain axis - Feng, Pengya; Zhao, Shuai; Zhang, Yangyang; Li, Enyao (Frontiers in Microbiology, 2023)
Autism spectrum disorder (ASD) is a class of neurodevelopmental conditions with a large societal impact worldwide. The evidence suggesting a link between the pathogenesis of ASD and gut-brain-axis dysregulation, but it is unknown that probiotic therapy for ASD and its accompanying gastrointestinal problems based on the gut-brain axis. Therefore, we performed an analysis for ASD based on preclinical and clinical research to give a comprehensive synthesis of published evidence of potential mechanism for ASD. On the one hand, this review aims to elucidate the communications between gastrointestinal abnormalities and ASD. Accordingly, we will also discuss the gut microbiota dysbiosis regarding gut-brain axis dysfunction as a target according to recent literature. On the other hand, this review suggests the administration of probiotics to regulate gut-brain axis might, therefore, be a useful novel therapeutic tool to improve gastrointestinal symptoms, ameliorate ASD related behavioral symptoms, restore gut microbiota composition, reduce inflammation, and restore intestinal barrier function in humans and animal models. This review suggests that targeting the microbiota by altering agents such as probiotics may represent an approach for treating subsets of individuals with ASD.